Postoperative results of 407 patients submitted to Doppler-guided transanal hemorrhoidal dearterialization - Rotta,Carlos Mateus (2019)
ABSTRACT Introduction: The treatment of hemorrhoidal disease by conventional technique is associated with significant morbidity, mainly represented by the postoperative pain and the late return to daily activities. A technique of hemorrhoidal dearterialization associated with rectal mucopexy is a minimal invasive surgical option that has been used to treat the hemorrhoidal disease and reduce its inconveniences. Objective: To analyze the seven-year results of hemorrhoidal dearterialization associated with rectal mucopexy in the treatment of hemorrhoidal disease. Methods: This study analyzed 407 patients with hemorrhoids grade II, III and IV, who underwent the technique of hemorrhoidal dearterialization in the Luzia de Pinho Melo Hospital, during the period between December 2010 and December 2017. Twenty-seven patients (6.6%) had hemorrhoidal disease of the grade II, 240 (59.0%) grade III, and 117 (28.8%) grade IV. In 23 patients (5.7%), the grade was not found. All patients were operated by the same surgeon under spinal anesthesia. The 407 patients underwent dearterialization, with a varying ligation of one to six arterial branches followed by rectal mucopexy by uninterrupted suture. Eighty-two (20.14%) required removal of concomitant perianal piles or external hemorrhoids and/or fibrosed. In the postoperative follow-up the following parameters were evaluated: pain, tenesmus, bleeding, prolapse, thrombosis, and recurrence. Results: The tenesmus was postoperative complaint reported by 93.6% of patients. Forty-three (10.5%) presented intense tenesmus and 44 (22%), moderate to intense pain. Four (0.98%) patients presented more intense bleeding in postoperative follow up; none of the patients required blood transfusions. The prolapse occurred in 18 (4.42%) patients, thrombosis in 11 (2.7%), and there were 19 (4.67%) recurrences that were reoperated in this period. Conclusion: The hemorrhoidal dearterialization technique presents good results, with light and easy-to-resolve complications and little postoperative pain.